Biological hydroxyapatite thin films synthesized by pulsed laser deposition - (:unkn) unknown (NATL INST OPTOELECTRONICS, 2013)
We report on biological hydroxyapatite (HA) thin films of human (dentine, DHA) and animal (bovine, BHA and ovine, OHA) synthesized by PLD. XRD studies evidenced monophasic HA structure of films, with crystallinity degree influenced by the biological origin. SEM investigations evidenced particulates with a mean size of similar to 2 mu m. EDS analysis revealed the presence of Mg, Na, Cl, F and C besides the majoritary Ca and P. OHA thin films exhibited higher adherence to substrate as compared to DHA. Based upon performances and low cost manufacturing, these biomaterials could develop into a valuable competitor to commercial HA for implantology applications.
Keywords: Biological hydroxyapatite thin films; Bone oligoelements; High adherence; Pulsed Laser Deposition; ELECTROPHORETIC DEPOSITION; COMPOSITE COATINGS; STAINLESS-STEEL; SOL-GEL; LAYERS; SPRAY